Analisa Kinerja Mesin Pembangkit Listrik Tenaga Gas Unit 1 Blok 1 di PT. Indonesia Power Grati POMU - Putra Damara A.W, A.A.N.; Wijaya Kusuma, I.G.B.; Sri Komaladewi, A.A.I.A. (Teknik Desain Mekanika, 2021)
Abstract PLTG PT. Indonesia Power Grati POMU is a power plant connected to the Java-Bali interconnection system. The Block 1 Unit 1 power plant engine uses a gas turbine produced by Mitsubishi Heavy Industries Japan in 1995 and began operation in 1997. The power plant engine operates using fuel in the form of natural gas. Based on these conditions, this research will analyze the comparison of installed capacity with actual capacity as well as shrinkage of power generation after 23 years of operation. The analysis is carried out by calculating the performance parameters of the power plant engine. The parameters referred to are compressor work, turbine work, nett work, heat intake, thermal efficiency, net power, specific fuel consumption, generation price, and the resulting power depreciation. After 23 years of operation there was an increase in compressor work of 237.16 kJ/kg, an increase in turbine work of 103.13 kJ/kg, a decrease in net work of 20.36 kJ/kg, an increase in heat intake of 30.99 kJ/kg, a decrease in efficiency of 3.74 %, and an increase in specific fuel consumption by 0.0093 kg/kWh. While the power depreciation that occurred was 2,592.28 kW or 2.87 %. As a result of the reduced power generated, the company suffered a loss of Rp. 32.799.901.053,57 /year. One of the causes of the decrease in the performance of the power plant engine is material degradation. Keywords : Analysis, Performance, Gas Turbines